Effect of Jasmonic Acid on Germination Dormant and Nondormant Apple Seeds - YILDIZ, KENAN; YAZICI, CENK; MURADOGLU, FERHAD (Asian Journal of Chemistry, 2010)
Jasmonic acid clearly stimulated germination of dormant apple seeds. However, in the seeds stratified for 30 and more days, some concentration of jasmonic acid seemed as inhibiting, generally, jasmonic acid was found ineffective. The treatment of seeds with jasmonic acid not only increased germination level, but also accelerated germination of dormant seeds according to control seeds. On the other hand, jasmonic acid delayed the germination of seeds stratified for particular period. The retarding effect of jasmonic acid on germination was clearer in seeds stratified for 90 d. Although jasmonic acid stimulated germination some degree, but it did not found as effective as stratification under cold condition in removal of dormancy in apple seeds.